Effect of green manure and plant density on correlation between rhizospheric bio-chemical properties and rice (Oryza sativa) yield - Kaur, Jaspreet; Gosal, S K; Walia, S S (The Indian Journal of Agricultural Sciences, 2020)
The present investigation was carried out to evaluate the effect of application of green manure along with varying plant density on microbial population and soil enzymatic activities of rhizospheric soil as well as on yield of rice (Oryza sativa L.)during year 2013–14. Application of green manures @15 t/ha and increased plant density up to 44 plants/m2 positively enhanced microbial population in the soil. Correlation among different microbial population, soil enzymatic activities and soil nutrient status in different treatments irrespective of the time intervals showed that the treatments with higher plant density along with green manure showed a significant positive correlation between dehydrogenase enzyme and bacterial as well as with fungal population. On contrary, treatment having sole application of inorganic fertilizer with 22 plants/m2; actinomycetes and bacterial population had significant positive correlation with dehydrogenase activity whereas fungal population showed a negative relationship. The soil urease and alkaline phosphatase activity had positive correlation with bacterial and fungal population in all treatments except the treatment with 22 plants/ m2 + recommended inorganic fertilizers. There was significant negative correlation between fungal population and diazotrophic population in all treatments. The plant height and various yield attributes were significantly higher in treatment having green manure (15 t/ha) + 44 plants/m2+ recommended NPK. Thus, above finding revealed that the agronomic practices (green manure and increased plant density) significantly improved the interaction of microbial population and soil enzymatic activities in rhizospheric soil which in turn affect the soil fertility as well as rice yield.